Targeting thromboinflammation in COVID-19 – A narrative review of the potential of C1 inhibitor to prevent disease progression. (October 2022) - Urwyler, Pascal; Moser, Stephan; Trendelenburg, Marten; Sendi, Parham; Osthoff, Michael
Abstract: Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 is associated with a clinical spectrum ranging from asymptomatic carriers to critically ill patients with complications including thromboembolic events, myocardial injury, multisystemic inflammatory syndromes and death. Since the beginning of the pandemic several therapeutic options emerged, with a multitude of randomized trials, changing the medical landscape of COVID-19. The effect of various monoclonal antibodies, antiviral, anti-inflammatory and anticoagulation drugs have been studied, and to some extent, implemented into clinical practice. In addition, a multitude of trials improved the understanding of the disease and emerging evidence points towards a significant role of the complement system, kallikrein-kinin, and contact activation system as drivers of disease in severe COVID-19. Despite their involvement in COVID-19, treatments targeting these plasmatic cascades have neither been systematically studied nor introduced into clinical practice, and randomized studies with regards to these treatments are scarce. Given the multiple-action, multiple-target nature of C1 inhibitor (C1-INH), the natural inhibitor of these cascades, this drug may be an interesting candidate to prevent disease progression and combat thromboinflammation in COVID-19. This narrative review will discuss the current evidence with regards to the involvement of these plasmatic cascades as well as endothelial cells in COVID-19. Furthermore, we summarize the evidence of C1-INH in COVID-19 and potential benefits and pitfalls of C1-INH treatment in COVID-19. Highlights: Aberrant activation of the complement system has been implicated in severe COVID-19. Thromboinflammation is also driven by the contact activation system. Drug candidates should interfere with these cascades to dampen inflammation. C1 inhibitor levels are increased in COVID-19 patients. Results from C1-INH trials in COVID-19 patients may clarify its role in COVID-19.